Photosynthesis and daily forage productivity of Tanzania guinea grass pastures under rotational stocking - Braga, Gustavo José; Mello, Alexandre Carneiro Leão de; Pedreira, Carlos Guilherme Silveira; Medeiros, Henrique Rocha de (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this study was to evaluate the effects of grazing intensity on forage accumulation rate and on net leaf photosynthesis of Tanzania guinea grass (Panicum maximum Jacq.) pastures under rotational stocking. The experiment was carried out from November 1999 to October 2000, in a randomized complete block experimental design, with four replications. Treatments were three levels of residual green forage biomass (1,000, 2,500, and 4,000 kg ha-1) in grazing cycles of 36 days (33 days of rest and 3 days of grazing). Forage accumulation rate was not affected by grazing intensities, and it was highest in the first 11 days of regrowth during the periods of the highest temperatures. Net leaf photosynthesis was not affected by grazing intensity (mean 23.2 mmol m-2 s-1 CO2) and increased during regrowth with the highest values between the 11th and the 22nd days of rest, depending on the season of the year. Net leaf photosynthesis was correlated with sward structure changes, during leaf development. The use of fixed rest periods avoided alterations of forage accumulation rate caused by grazing intensity.
Keywords: Panicum maximum; sward height; sward structure; leaf area index; forage mass